CORRELATIONS OF GIVING DESINFECTION (ALCOHOL SWAB) WHEN GIVING INTRAVEIN INJECTION WITH PHLEBITIS - Rindayanti, Rindayati (Universitas Airlangga, 2020)
Introduction: Phlebitis is inflammation of the veins caused by chemical irritations of additives and drugs that are given intravenously. Phlebitis is characterized by the presence of a red and warm area around the area of stabbing or along the vein. This study aims to determine the effect of disinfection (alcohol swab) on intravenous bolus injection with phlebitis. Methods: The research design used in this study is pre-experiment (Static Group Comparison). In this study the population was all patients who received intravenous bolus therapy. The sample in this study were some patients who received intravenous bolus therapy who met the inclusion criteria. Sampling in this study was simple random sampling with a total sample of 52 respondents. Results: From the Chi Square Test x2 = 17,333 and p = 0,00 because p <0. (0,00 <0,05) then H0 is rejected which means there is an influence of disinfection of alcohol swab during intravenous bolus injection with phlebitis occurrence. The number of respondents in the control group who did not / without using alcohol swab almost all respondents had phlebitis (84.6%) and only a small number did not occur phlebitis (15.3%) while respondents who were given alcohol swab during injection via intravenous bolus almost all phlebitis did not occur (92.3%) and a small proportion occurred phlebitis (7.6%). Conclusion: Based on the results of the study, can be concluded that there is an influence of alcohol swab during intravenous injection with the occurrence of plebebitis. The effort that can be done to prevent phlebitis is aseptic technique in the area of insertion and disinfection that is strong in medical devices, observation of signs and symptoms of phlebitis, infusion catheter must be replaced if it is installed > 27 hours.